SYAIR NASIHAT DALAM SAWER PENGANTIN PERKAWINAN ADAT SUNDA KABUPATEN ROKAN HULU (KAJIAN SEMIOTIK) - Susi Susanti; Elmustian Rahman; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the poetry counsel in Sundanese traditional marriage bride sawer rokan district upstream semiotic studies. This study also discusses describe the signs, where signs contained in this research that icons, indexes and symbols on the poem in a customary marriage bride sawer Sunda. This study used a qualitative approach and descriptive method that aims to describe how the poem Sawer bride marriage advice in there Sunda. The research subject is the text sawer Sundanese culture. The results of this research is the identification, analysis and conclusions from each of its verses. From the research found that there are 100 stanzas sawer bride. From these results more icons to the data which is equal to 169, the data symbol 52, and index 6 data.KeyWords: Advice Poetry, Sawer Bride, Semiotic Studies.